(untitled) (ALPHA. Journal of Arts, Literature and Philosophy, 2025)
Thucydides in his narration of the Peloponnesian War gives a fundamental role to the action of individuals. For Leo Strauss, this importance is not merely historical. What the Athenian author seeks is to give universal lessons about political action. In this way, the characters are also archetypes and it is through the study of these that the aspiring politician can learn how to achieve better action, in addition to showing how to balance issues such as religion and politics.